Development and evaluation of a service leadership subject in a blended learning mode. - Xiaoqin Zhu; Shek, Daniel T. L.; Diya Dou; Wenyu Chai (International Journal of Child & Adolescent Health, 2020)
In view of the emergence of service economies in the global context, it is important to promote service leadership education in universities. In Hong Kong, many studies showed that service leadership education could successfully promote university students' service leadership attributes (competence, character, and care) and foster their wellbeing. To benefit more students and enrich their learning experiences, there is a need to develop blended learning tools in addition to traditional classroom-based service leadership education in Hong Kong. In this article, we outline the development of a leadership subject in blendedlearning mode. Preliminary findings suggest that participating students generally showed positive perceptions of the course, instructors, and course benefits. Besides, students' service leadership qualities and well-being showed positive changes after completing the course. Limitations of the evaluation findings and challenges of implementing a blended service leadership course are discussed.